2018
DOI: 10.3892/ijo.2018.4634
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory role of AMP‑activated protein kinase in necroptosis of HCT116 colon cancer cells with p53 null mutation under nutrient starvation

Abstract: Simultaneous induction of other types of programmed cell death, alongside apoptosis, in cancer cells may be considered an attractive strategy for the development of more effective anticancer therapies. The present study aimed to investigate the role of AMP-activated protein kinase (AMPK) in nutrient/serum starvation-induced necroptosis, which is a programmed form of necrosis, in the presence or absence of p53. The present study detected higher cell proliferation and lower cell death rates in the HCT116 human c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 66 publications
2
8
0
Order By: Relevance
“…Our data indicated that dorsomorphin decreased the levels of p‐AKT, p‐70s6k, and cyclin D1. In line with our data, another recent study showed that inhibition of AMPK, by dorsomorphin, accelerated necroptosis by increasing the level of ROS in HCT116 p53−/− cells …”
Section: Discussionsupporting
confidence: 93%
“…Our data indicated that dorsomorphin decreased the levels of p‐AKT, p‐70s6k, and cyclin D1. In line with our data, another recent study showed that inhibition of AMPK, by dorsomorphin, accelerated necroptosis by increasing the level of ROS in HCT116 p53−/− cells …”
Section: Discussionsupporting
confidence: 93%
“…In the case of cancers, cells bearing wild-type TP53 gene expressing functional p53 protein is regarded to be a strong tumor suppressor while, mutated TP53 gene expressing a mutant p53 protein with GOF tactically overcomes the cell death pathways and make cells resistant to chemotherapeutic drug treatments ( 41 , 42 ). The p53 mutations being one of the most frequently occurring mutations in colon cancer with its proven role in inducing resistance to therapeutic drugs, the mutant p53 marks itself as a prominent predictive molecular marker for chemoresistance ( 43 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have described the role of autophagy in tumor chemoresistance as context-dependent ( 42 ) suggesting that wild-type p53 induces autophagy ( 81 ), whereas mutant p53 represses ( 82 , 83 ) it. However, studies depicting autophagy as a cytoprotective mechanism of chemoresistance in colon cancer cells being linked their p53 status are limited or nearly nil.…”
Section: Discussionmentioning
confidence: 99%
“…The mixed cells were loaded onto EVE TM slides (Nano-EnTek-Inc.). To investigate the number of total cells, live-cells and dead-cells followed a previous study [61]. Cell cytotoxicity percentage was calculated by using percentage formula for live-cells in the treated group versus live cells in control group in different concentration of ECPU-0001 (0, 1, 2, 3 and 4 μM ECPU-0001 and DMSO) after culturing in complete media (CM).…”
Section: Methodsmentioning
confidence: 99%